Saving Lucas Biggs - De los Santos, Marisa, 1966-; Teague, David (Harper, 2015)
When her father is given the death sentence by the cruel Judge Lucas Biggs, thirteen-year-old Margaret O'Malley uses her family's forbidden ability to time travel back to the past in order to change the character of Lucas Biggs, so that he will not become the kind of judge who would sentence her innocent father.